Peranan Kantor Urusan Agama (KUA) Dalam Menangani Pernikahan dan Kepentingan Keagamaan Masyarakat di Kecamatan Medan Timur - Abdul Halim; Suci Hayani Bugis; Istiqomah Ayu Syahputri; Fatimah Azzahro Harahap; Arbiatun Hidayah; Ersa Yusasni; Miftahul Jannah; Kurniawan Dito; Zoelfikar Azri Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The Office of Religious Affairs is one of the government agencies or institutions that carry out the duties and functions of the Ministry of Religion in the field of Islamic religion. The function of these agencies or institutions is to provide services to the community in the surrounding environment in terms of religious guidance and services, such as guidance for sakinah family marriages, wedding services, SOPs for building houses of worship, SOPs for endowments, courses for prospective brides and newlyweds (suscatin), services duplicate quotations of marriage certificates, SOP for depositing PNBP NR, and marriage administration services. In the service process, the Office of Religious Affairs as a government agency or institution documents all activities it does, including the process of processing data archives. This research is concerned with the role of the East Medan District Office of Religious Affairs in dealing with marriage issues. Keywords: The Office of Religious Affairs, Wedding, Interest